2009
DOI: 10.2188/jea.je20080076
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Psychological Distress in a Community-Dwelling Japanese Population: The Ohsaki Cohort 2006 Study

Abstract: BackgroundIn Asia, there has been no population-based epidemiological study using the K6, a 6-item instrument that assesses nonspecific psychological distress.MethodsUsing cross-sectional data from 2006, we studied 43 716 (20 168 men and 23 548 women) community-dwelling people aged 40 years or older living in Japan. We examined the association between psychological distress and demographic, medical, lifestyle, and social factors by using the K6, with psychological distress defined as 13 or more points out of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
61
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 24 publications
16
61
5
Order By: Relevance
“…The association between age and psychological distress is not clear in the general Japanese population [19]. Interestingly, our results are in contrast to those of Toyabe et al [2], who clearly showed that General Health Questionnaire (GHQ)-assessed psychological distress was higher in older adults living in temporary housing 5 months after the NiigataChuetsu earthquake.…”
Section: Discussioncontrasting
confidence: 99%
“…The association between age and psychological distress is not clear in the general Japanese population [19]. Interestingly, our results are in contrast to those of Toyabe et al [2], who clearly showed that General Health Questionnaire (GHQ)-assessed psychological distress was higher in older adults living in temporary housing 5 months after the NiigataChuetsu earthquake.…”
Section: Discussioncontrasting
confidence: 99%
“…It roughly ranges between 5% and 27% in the general population (Benzeval and Judge 2001, Chittleborough et al 2011, Gispert et al 2003, Kuriyama et al 2009, Phongsavan et al 2006) but it can reach higher levels in some segments of the population exposed to specific risk factors such as workers facing stressful work conditions and immigrants who must adapt to the host country while holding family responsibilities in the homeland. The International Labour Office stated that psychological distress affected between 15 and 20% of workers in Europe and North America (International Labour Office 2000) and one out of five workers may experience repeated episodes of psychological distress (Marchand, Demers, and Durand 2005a).…”
Section: Prevalence Of Psychological Distressmentioning
confidence: 99%
“…Some factors are not considered in this summary of the epidemiology of distress either because the evidence is lacking or because they are usually interpreted in terms of social and economic factors that can be assessed more directly. Health behaviour such as smoking and alcohol intake are associated with increased odds and mean level of distress (Chittleborough et al 2011, Kuriyama et al 2009, , Myklestad, 2011Phongsavan et al 2006) but the interpretation of this association is awkward. Smoking and alcohol may be a form of selfmedication to dilute the burden of distress but they may also generate some distress.…”
Section: In the General Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown, as compared to men, women had a higher risk of psychological distress (Pratt et al, 2007;Hagman et al, 2008;Kuriyama et al, 2009). They suggested that many factors, such as personality, coping skills, and sociocultural roles, play a direct role in psychiatric disorders (Piccinelli et al, 2000;Afifi et al, 2007).…”
Section: 309 Factors Associated With Psychological Characteristics Imentioning
confidence: 99%